Lattice Tree versus Dynamic Programming in Real Option Analysis: Hui Zhao, Pairote Sattayatham, Bhusana Premanode - Team, Support (Thai Journal of Mathematics, 2016)
This paper discusses the influences of the Chinese cellulosic ethanol policybased on lattice tree and dynamic programming approaches in real option analysis.Based on the basic hypothesis of double stochastic variables and two constructionstages, the empirical conclusions are shown in each real option model respectively.Because of the existence of by-products, the influence of the subsidy is not obviouslyto the optimal decisions. Thus, improving the technology to fine the highvalue by-products is the effective way to increase the revenues.